An update on the profile of children with affirmative responses to the 2021 Census questions on difficulties with activities of daily living - Thomas Charters; Rubab Arim; Leanne Findlay (Economic and Social Reports)
This study presents an updated sociodemographic profile of children aged 0 to 14 years with affirmative responses largely based on parent reports to the questions on the 2021 Census long-form questionnaire about difficulties with activities of daily living.